Entrepreneurial Passion and Entrepreneurial Success—The Role of Psychological Capital and Entrepreneurial Policy Support - Hu, Wei; Xu, Yan; Zhao, Fuqiang; Chen, Yun (Frontiers in Psychology, 2022)
Entrepreneurship success is the ultimate goal pursued by entrepreneurs, and entrepreneurial passion is also considered an indispensable and important element on the road to entrepreneurial success. However, the internal influence mechanism of entrepreneurial passion on entrepreneurial success is still insufficient in academic circles. In view of this, based on the theory of social information processing, this research analyses the internal mechanism of entrepreneurial passion through individual psychological capital on entrepreneurial success and the promotion of external entrepreneurial policy support. Through a multi-time and multi-source questionnaire survey of 455 entrepreneurs in entrepreneurship parks and entrepreneurship centers in Wuhan, Guangdong, Shanghai, and other places, the research results show that entrepreneurial passion can increase individual psychological capital and positively affect entrepreneurial success; psychological capital mediates the relationship between individual entrepreneurial passion and entrepreneurial success. Entrepreneurship policy support at the environmental level can promote the effect of entrepreneurial passion on the accumulation of psychological capital, and promote the transformation of entrepreneurial passion into entrepreneurial success through psychological capital. The above research results are helpful to the accumulation of entrepreneurs’ psychological capital and provide a useful reference for entrepreneurial success.